The Hollow Ring of Donor Commitment: Country Concentration and the Decoupling of Aid-Effectiveness Norms from Donor Practice - Brown, Stephen; Swiss, Liam (Université d'Ottawa | University of Ottawa, 2013)
The fragmentation of a donor's foreign aid across too many recipient countries is widely believed to be detrimental to aid effectiveness. This article explores the origins of a new norm – recipient concentration – and assesses the extent to which it can be expected to improve aid effectiveness. It also examines 23 donors' actual record of country concentration, and finds that, though there are some potential explanations for donors' behaviour, their collective failure to implement country concentration has very little consequence in theory or in practice.
Keywords: Aid; donors; concentration; fragmentation; decoupling; norms